Facilitated folding of actins and tubulins occurs via a nucleotide-dependent interaction between cytoplasmic chaperonin and distinctive folding intermediates. - Melki, R (1994)
In the cytoplasm of eukaryotes, the folding of actins and tubulins is facilitated via interaction with a heteromeric toroidal complex (cytoplasmic chaperonin). The folding reaction consists of the formation of a binary complex between the unfolded target protein and the chaperonin, followed by the ultimate release of the native polypeptide in an ATP-dependent reaction. Here we show that the mitochondrial chaperonin (cpn60) and the cytoplasmic chaperonin both recognize a range of target proteins with different relative affinities; however, the cytoplasmic chaperonin shows the highest affinity for intermediates derived from unfolded tubulins and actins. These high-affinity actin and tubulin folding intermediates are distinct from the "molten globule" intermediates formed by noncytoskeletal target proteins in that they form relatively slowly. We show that the interaction between cytoplasmic chaperonin and unfolded target proteins depends on the chaperonin being in its ADP-bound state and that the release of the target protein occurs after a transition of the chaperonin to the ATP-bound state. Our data suggest a model in which ATP hydrolysis acts as a switch between conformational forms of the cytoplasmic chaperonin that interact either strongly or weakly with unfolded substrates.